2019
DOI: 10.3389/fendo.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia Following Ureteric Stent Placement in a Patient With Type 2 Diabetes Treated With Canagliflozin

Abstract: A 38-year-old female patient with well-controlled type 2 diabetes mellitus treated with canagliflozin underwent ureteral stent placement for obstructive renal calculi. Ten days following ureteroscopy and ureteral stenting, she developed fevers and blood cultures grew Candida glabrata (C. glabrata). The patient was successfully treated with an extended course of broad-spectrum antibiotics and antifungal agents. The clinical presentation of candidemia is indistinguishable from bacteremia resulting in delay in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Candidaemia after ureteric instrumentation may in part be related to the formation of a biofilm on stents 39–41 . There are also reports in association with new agents for treatment of diabetes that cause marked glycosuria 42 . The urinary tract is being recognised as an increasingly important source of candidaemia and prompt removal of IDC when possible is key.…”
Section: Discussionmentioning
confidence: 99%
“…Candidaemia after ureteric instrumentation may in part be related to the formation of a biofilm on stents 39–41 . There are also reports in association with new agents for treatment of diabetes that cause marked glycosuria 42 . The urinary tract is being recognised as an increasingly important source of candidaemia and prompt removal of IDC when possible is key.…”
Section: Discussionmentioning
confidence: 99%
“…Devices such as stents and catheters have been known to facilitate biofilm formation with Candida spp., and the degree of biofilm formation is associated with enhanced virulence [ 13 ]. Additionally, from a previously conducted retrospective study, researchers identified “underlying risk factors like urinary tract abnormalities (88%), use of antibiotics within 1 week (85%), underlying malignancies (73%), urinary tract obstruction (73%), and prior urological procedure within 2 weeks (73%)” may increase susceptibility to candidemia from a urinary source [ 12 , 14 ]. Our patient not only underwent urological procedures but also urinary tract obstruction with his initial diagnosis of nephrolithiasis and was empirically treated with ceftriaxone for potential urinary tract infection at admission as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient not only underwent urological procedures but also urinary tract obstruction with his initial diagnosis of nephrolithiasis and was empirically treated with ceftriaxone for potential urinary tract infection at admission as well. He was also a diabetic patient, despite having well-controlled blood glucose levels, which naturally predisposes to candiduria and thus candidemia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation